Quantitative spore composition of endomycorrhizal fungi at lower reach of Ili (Kerbulak boundary) (Eurasian Journal of Ecology, 2016)
A quantity of spores of endomycorrhizzal fungi from plant associations at lower Ili correlates with soil humidity: the most found at sites with moderate humidity (moisture content 8.99 %), the least - at sites with low humidity (soil moisture content 1.26-2.26 %). Excessive humidity led to two-fold decrease in spore number in comparison to sites with moderate humidity.
Keywords: edomycorhiza; fungal spores; f. Glomus; Gigaspora; soil humidity